How Do You Manage Change in Organizations? Training, Development, Innovation, and Their Relationships - Sartori, Riccardo; Costantini, Arianna; Ceschi, Andrea; Tommasi, Francesco (Frontiers in Psychology, 2018)
The article aims to be a reflective paper on the interconnected concepts of training, development and innovation and the potential they have in dealing with change in organizations. We call change both the process through which something becomes different and the result of that process. Change management is the expression used to define the complex of activities, functions, and tools (such as training courses) through which an organization deals with the introduction of something new that is relevant for both its survival and growth. Training and development are labels used to define those educational activities implemented in organizations to empower the competences of workers, employees and managers in the lifelong learning perspective of improving their performance. Consequently, we define competences as those personal characteristics that allow people to be effective in the changing contexts of both workplace and everyday life. They are also necessary in organizational innovation, which is the process of transforming ideas or inventions into goods or services that generate value and for which customers will pay. Training, development, and innovation are three different but interconnected functions by which organizations manage change. What is the state of the art of the literature dealing with these topics? Here, is a critical review on the matter.